Experimental study on performance of a solar-air source heat pump system in severe external conditions and switchover of different functions. (August 2016) - Ni, Long; Qv, Dehu; Shang, Runxin; Yao, Yang; Niu, Fuxin; Hu, Wenju
Abstract: A phase change material (PCM) based solar-assisted air source heat pump (PCM-SAHP) composed of an air source heat pump (ASHP), a PCM unit, and a solar thermal collector is proposed. In this work, the system performance is experimentally tested in the severe external conditions, and the effect of switchover of different functions on the system stability is examined as well. The results indicate that a great improvement in both the system efficiency and heating/cooling capacity in the severely external conditions is achieved by the application of the PCM unit in the SAHP cycle. The outdoor air temperature throughout a whole day-night cycle has a significant effect on the system cooling performance. In contrast, the solar-heated hot water temperature, rather than the ambient temperature, exerts a great influence on the system heating performance. In order to maximize the system capacity and efficiency, how to match the capacity of the PCM unit and the compressor is crucial. In addition, the effect of switchover of different functions on the system stability is unapparent. Finally, the compatibility of the PCM unit with the SAHP system is concluded based on kinds of individual approach.